ADHD: Attention Deficit Disorder and Hyperactivity (Research, Society and Development, 2021)
This research aims to review the literature on ADHD - Attention Deficit Hyperactivity Disorder - Analyze the knowledge of professionals about ADHD; and through literary review to analyze the problems that students face for having ADHD. During the research, answer the question of what is the importance of nursing care focused on the care of students with ADHD? The methodology will be bibliographical through articles, electronic books, magazines and monographs already published on the internet in order to achieve the expected result. It begins with a brief approach to Attention Deficit Hyperactivity Disorder by reviewing the literature on the subject, bringing to the research positions related to ADHD by specialists such as some authors such as QUINTERO, (2011), Martínez, (2019), LEITE and OLIVEIRA, (2015) and Richter (2012). The main results found were: that the forms of treatment can be different, starting with psychotherapies and drugs, they also seek to carry out interventions regarding social life, carrying out conversations with parents, about how to put into action some strategies to help deal with your children.